Hydroethanolic leaf extract of Acacia auriculiformis exhibited antidiabetic and antioxidant activities. Issue 1 (31st December 2022) - Sharma, Divya; Verma, Surender; Kumar, Sunil; Singh, Jitender; Kumar, Ravi; Jangra, Ashok; Kumar, Dinesh
ABSTRACT: Acacia auriculiformis A. Cunn. Ex. Benth (family: Fabaceae) is traditionally used as a folk remedy for diabetes in Central Africa. The present study was intended to evaluate the antioxidant and enzyme inhibitory potential of hydroethanolic leaf extract (HEAA) and its fractions (n-hexane, chloroform and ethyl acetate) at different concentrations (100–500 μg/ml) to justify its role in diabetes. The leaf extract (HEAA) and its ethyl acetate fraction (EFAA) showed maximum scavenging effect (60.43 ± 0.11, 50.87 ± 0.31) at 500 µg/ml, respectively. However, in enzyme inhibitory assays, the HEAA extract and EFAA among the fractions exhibited maximum inhibition against α‑amylase (61.69 ± 0.05, 53.87 ± 0.33), α‑glucosidase (63.34 ± 0.12, 58.46 ± 0.90) and pancreatic lipase (51.77 ± 0.15, 49.87 ± 0.31), respectively, at 500 µg/ml when compared with standard. The IC50 values of HEAA and EFAA against α‑amylase (3.35 and 4.48, respectively), α‑glucosidase (3.36 and 4.04, respectively) and pancreatic lipase (4.47 and 5.07, respectively) are also significant. The results suggest that HEAA possesses good antioxidant and enzyme inhibitory potential, which in turn might be responsible for its antidiabetic effect. Graphical Abstract: uf0001